The Relationship between audit adjustments and audit quality in Iraq - Mahdi Salehi; Mohammed Ibrahim Jebur; Saleh Orfizadeh; Ali Mohammed Abbas Aljahnabi (Journal of Risk and Financial Management, 2022)
The present research aims to assess the potential impact of audit adjustments on the audit quality for the listed companies on the Iraqi Stock Exchange. In other words, this research attempts to answer whether the audit adjustments can improve the audit quality or not. To achieve the objectives, a multivariate regression model was employed to test the hypotheses. The research hypotheses were tested using a sample of 35 listed firms on the Iraqi Stock Exchange for 2014-2020 by exploiting a multiple regression model based on the panel data technique. The research findings indicate a positive and significant relationship between audit adjustments and quality. Such findings demonstrate that audit adjustment might be considered a quality factor for audit services. Since no research has addressed such a subject in Iraq, the study can provide helpful information for the equity owners, board of directors, and audit firms, contributing to developing science and knowledge in the auditing field of study.
Keywords: 650; audit quality; audit adjustments